2019
DOI: 10.1016/j.jhydrol.2019.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-term flood-hazard modeling for coastal areas using InSAR measurements and a hydrodynamic model: The case study of Lingang New City, Shanghai

Abstract: In this paper, we study long-term coastal flood risk of Lingang New City, Shanghai, considering 100-and 1000-year coastal flood return periods, local seal-level rise projections, and long-term ground subsidence projections. TanDEM-X satellite data acquired in 2012 were used to generate a high-resolution topography map, and multi-sensor InSAR displacement time-series were used to obtain ground deformation rates between 2007-2017. Both data sets were then used to project ground deformation rates for the 2030s an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 80 publications
0
28
0
Order By: Relevance
“…We apply a Differential Synthetic Aperture Radar Interferometry (DInSAR)-based geotechnical model developed by Pepe et al (2016), Yin et al (2019), and Zhao et al (2015) to predict the cumulative deformation of seawall (i.e., sea dike) along the Shanghai coastline. First, we use multitemporal and multisatellite synthetic aperture radar (SAR) images to retrieve the seawall deformation history and rates in Shanghai.…”
Section: Seawall Deformation Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…We apply a Differential Synthetic Aperture Radar Interferometry (DInSAR)-based geotechnical model developed by Pepe et al (2016), Yin et al (2019), and Zhao et al (2015) to predict the cumulative deformation of seawall (i.e., sea dike) along the Shanghai coastline. First, we use multitemporal and multisatellite synthetic aperture radar (SAR) images to retrieve the seawall deformation history and rates in Shanghai.…”
Section: Seawall Deformation Predictionmentioning
confidence: 99%
“…A full description of the model structure and parameterization can be found in Yu and Lane (2011). FloodMap-Inertial, as well as its earlier diffusion-based version (FloodMap) (Yu & Lane, 2006), have been tested and implemented in fluvial, pluvial, and coastal environments in Shanghai (Yin et al, 2013(Yin et al, , 2015(Yin et al, , 2019, achieving a good level of performance for flood prediction. A recent validation study (Yin et al, 2016), comparing model output against observed inundation in New York City, further indicated that the city-scale and street-level modeling framework similar to that used here is capable of high predictive skill for inland flooding.…”
Section: Flood Inundation Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mechanisms related to sea level changes include friction-altering changes in water depth, resonance changes in harbor regions [56], or stratification changes induced by increased upper-ocean warming [8], which may modify internal tides [57]. On a shorter timescale, seasonal tidal variations can be due to rapid changes in water column stratification or by seasonal river flow characteristics [18]. The high sensitivity of tides relative to sea level changes also suggests increased impacts of storm-induced flooding since both tides and storm surge are long-wave processes [56,58].…”
Section: Research Aimsmentioning
confidence: 99%
“…The principal results of the investigations performed within our Dragon IV project have been published in peer-reviewed journals over the last five years [14][15][16][17][18][19][20][21][22][23][24][25][26][27] and represent the starting point for future studies to be performed in the following years. We will summarize the main results of previous research related to this project in this article.…”
Section: Introductionmentioning
confidence: 99%